Financial Statement Fraud Of Energy Sector Companies: Analysis Of The Affecting Factors - Reschiwati, Reschiwati; Sani, Erma Tiara (Universitas Pamulang, 2024)
This research aims to analyze the influence of Financial Stability, External Pressure, Ineffective Supervision, Change of Auditor, Change of Director, and Frequency of CEO's Picture on Financial Report Fraud. The population is all energy sector companies listed on the Indonesia Stock Exchange for the period 2018 - 2022. The sample selection method was purposive, and the number of observations was found to be 155. Data analysis used Eviews 13 software. The novelty is, to further test variables that have no effect. as a moderating variable. The test results show that financial stability, external pressure, and change of directors influence financial statement fraud. However, ineffective supervision has no effect but is proven to be a moderator. Change of auditor and frequency of CEO photos do not affect financial statement fraud and are not proven to be moderating variables.